(untitled) (Research, Society and Development, 2024)
Objective: To understand aspects of the epidemiological profile and vaccination coverage of meningitis in children under 9 years of age in the metropolitan region of Maringá between 2018 and 2022. Methods: This research used data from the National Disease and Notification System to extract epidemiological information and structure the study quantitative and descriptive. Results: Children under 1 year of age, male and white are the most affected. Regarding etiology, viral meningitis was the most prevalent followed by bacterial. Considering the evolution of the disease, 94.39% were discharged from the hospital, 2.93% died due to worsening meningitis and 1.95% died from other causes. Regarding vaccination coverage between 2018 and 2022, it was found that the target of 95% for meningococcus C and pneumococcal vaccines was not achieved. Assessing the age range recommended by the National Immunization Program, it appears that low vaccination coverage means that children under 1 year of age are more susceptible to acquiring vaccine-preventable diseases. The data found are congruent with other studies highlighting the endemic course of meningitis in Brazil. Conclusions: It is concluded that meningitis has a high potential for transmission, pathogenicity, and possible neurological sequelae in children under 1 year of age, making it a public health problem. This disease can be prevented through vaccines made available by the Unified Health System. The importance of reflecting on strategies and actions to inform the population is highlighted, enabling increased adherence to vaccination coverage to combat this disease.